Análise do comportamento da cor de restaurações cerâmicas sem metal avaliadas por diferentes métodos: estudo clínico prospectivo - Martini, Ana Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The process of interpretation of color in thin ceramic restorations pre- and post-treatment is challenging. The evaluation methods of the results are diverse and literature is not clear in pointing out the most effective method. The question is even more relevant given the variation of the resin cement used. Purpose: After changing the type of resin cement used, the aim of this study was to evaluate the color behavior of ceramic restorations in teeth with aesthetic demand, over 1 year after treatment, with the help of different monitoring methods (spectrophotometer, photographs, videos and clinical assessment) in a longitudinal and prospective study. Materials and Methods: 28 patients were selected, for a total of 204 restored teeth (89 veneers, 57 crowns and 58 contact lenses). 76 restorations were cemented with Rely X veneer, 71 with Variolink veneer and 57 with Rely X U200. Color measurements were made with a spectrophotometer, digital photos and videos taken during treatment and periodic controls (initial, 30 days, 180 days and 1 year after cementation). Groups formed by outside observers (patients, students of 1st and last year of undergraduate, graduate students, and experts) evaluated, randomly, images obtained initially and after treatment, according to questions on satisfaction or not with the aesthetic outcome of the case. Results: The data obtained with the spectrophotometer were subjected to statistical tests which showed a significant difference only between the time periods; however, for all types of restoration, color stability was observed after a maximum of 180 days after cementation. There was no statistical difference between the satisfaction of different groups of outsiders observers with the aesthetic result of the cases for both the photos and for videos, although they videos have obtained the highest...

Introdução: O processo de interpretação da cor em restaurações cerâmicas delgadas pré e pós-tratamento é um desafio. Os métodos de avaliação dos resultados são diversos e a literatura não é clara em apontar o mais eficaz e eficiente. A questão é ainda mais relevante diante da variação do cimento resinoso utilizado. Proposição: Após variar o tipo de cimento resinoso utilizado, o objetivo deste estudo foi avaliar o comportamento da cor de restaurações cerâmicas em dentes com demanda estética, ao longo de 1 ano após o tratamento, com o auxílio de diferentes métodos de acompanhamento (espectrofotômetro, fotografias, vídeos e avaliação clínica) em um estudo clínico longitudinal e prospectivo. Materiais e Métodos: Foram selecionados 28 pacientes, perfazendo um total de 204 dentes restaurados (89 facetas laminadas, 57 coroas totais ou parciais e 58 lentes de contato). 76 restaurações foram cimentadas com Rely X veneer, 71 com Variolink veneer e 57 com Rely X U200. Foram realizadas mensurações de cor com espectrofotômetro, fotografias digitais e vídeos gravados no decorrer do tratamento e em controles periódicos (inicial, 30 dias, 180 dias e 1 ano após a cimentação). Grupos formados por observadores externos (pacientes, alunos de 1º e último ano de graduação, pós-graduandos e especialistas) avaliaram, aleatoriamente, as imagens obtidas inicialmente e ao final do tratamento, segundo perguntas sobre a satisfação ou não com o resultado estético do caso. Resultados: Os dados obtidos com o espectrofotômetro foram submetidos a testes estatísticos que revelaram diferença significativa apenas entre os tempos avaliados, contudo, para todos os tipos de restauração foi observada estabilidade de cor após, no máximo, 180 dias da cimentação. Não houve diferença estatística entre a satisfação dos diferentes grupos...
Keywords: Prótese dentária parcial fixa; Cor; Estética dentária; Cerâmicas odontológicas; Cimentos de resina; Denture, Partial, Fixed